Nowe obszary docelowe w migracji z Ukrainy do Polski: Przypadek Bydgoszczy i Wrocławia na tle innych miast - Agata Górny; Katarzyna Kołodziejczyk; Karolina Madej; Paweł Kaczmarczyk (University of Warsaw, Centre of Migration Research (CMR), 2019)
– The report demonstrates results of two surveys of Ukrainian migrants in Bydgoszcz and Wroclaw in 2018, as new destinations in Poland, with reference to earlier similar studies in Warsaw (2015) and Lublin (2016). It covers socio-demographic characteristics of migrants, their legal status, migration patterns, situation on the labour market and practices related to savings and financial transfers. Its main conclusion says about spatial diversification of migration from Ukraine to Poland on various layers. In particular, Wroclaw differs from Bydgoszcz with regard to more permanent character of migration - in terms of migration patterns, family situation, savings and financial transfers related behaviour - higher level of migrants' education and their better situation on the local labour market. These imply that Wroclaw is a unique case among the analysed towns sharing most similarities with a university town such as Lublin. Specificity of new migrants' destinations lies in relatively high shares of foreigners originating from Eastern Ukraine, activities of employment agencies and important role of industry in employment of a foreign labour. Conclusions of the report address also changes in migration from Ukraine to Poland in last years, referring additionally to a more recent study in Warsaw in 2017. After 2014, masculinisation of Ukrainian migration has grown and migrants' labour market situation has slightly improved accompanied by progressing diversification of sectors of migrants' employment. Also, apparently temporarity of Ukrainian migration to Poland has diminished, but much depends on the specificity of the given destination areas and local labour markets in this regard.
Keywords: 330; Ukrainian migrants; Wroclaw; Bydgoszcz; migration patterns; labour market